2020
DOI: 10.1111/mcn.13095
|View full text |Cite
|
Sign up to set email alerts
|

Child feeding practices and concerns: Thematic content analysis of Thai virtual communities

Abstract: Parents' child feeding practices are influenced not only by family but also by a broader circle of networks, including online groups. Peer-to-peer platforms such as Facebook groups facilitate a learning environment and may influence the transmission of user-generated content into practice. These digital data not only benefit participants but also offer new opportunities for researchers to study related phenomena. Therefore, this study employs thematic content analysis to investigate peer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Although television is the generally accessible mass media in Thailand, the internet or social media are the most common types of mass media from which our participants gained information related to prolonged breastfeeding. This finding is consistent with recent research, which has found that online support groups are a relatively new trend in Thailand, and Facebook has become a platform for Thai parents to seek informational and emotional support related to child feeding content [40]. Apart from health care professionals, husbands and maternal grandmothers were more frequently mentioned as influential persons with extended breastfeeding than friends.…”
Section: Discussionsupporting
confidence: 91%
“…Although television is the generally accessible mass media in Thailand, the internet or social media are the most common types of mass media from which our participants gained information related to prolonged breastfeeding. This finding is consistent with recent research, which has found that online support groups are a relatively new trend in Thailand, and Facebook has become a platform for Thai parents to seek informational and emotional support related to child feeding content [40]. Apart from health care professionals, husbands and maternal grandmothers were more frequently mentioned as influential persons with extended breastfeeding than friends.…”
Section: Discussionsupporting
confidence: 91%
“…Thematic content analysis (TCA) – a method for identifying, analysing and reporting patterns (themes) within data (Braun and Clarke, 2008: 79) – is an established method for studying online social interactions. Rather than allowing an in-depth analysis of a single story, it enables us to understand how, what and why the members of a group want to share in a common space like Facebook groups (Ahmed et al, 2017; Haik et al, 2019; Selman et al, 2021; Supthanasup et al, 2021). TCA has also been successfully used to analyse the primary purposes of the Facebook group used by immigrants (Baran, 2018; NurMuhammad et al, 2016).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Infants and preschoolers require adequate supervision regarding feeding practices, preferences and self-regulation in their diet (Haines et al, 2019). Hence the importance of professionals acting in accompanying family members and advising on good feeding habits from the beginning of life (Araújo et al, 2021), also discussing and guiding on the role of social media as a factor of interaction and search for information by family members, avoiding the influence of virtual communities that are not always made up of people with appropriate training to adequately address the subject (Supthanasup et al, 2021).…”
Section: Final Considerationsmentioning
confidence: 99%